Candidate gene associations with withdrawn behavior. (28th June 2013) - Rubin, David H.; Althoff, Robert R.; Ehli, Erik A.; Davies, Gareth E.; Rettew, David C.; Crehan, Eileen T.; Walkup, John T.; Hudziak, James J.
<x xml:space="preserve">Abstract</x> Background Social withdrawal is a core neuropsychiatric phenomenon in developmental psychopathology. Its presence predicts psychopathology across many domains, including depression, psychosis, autism, anxiety, and suicide. Withdrawn behavior is highly heritable, persistent, and characteristically worsens without intervention. To date, few studies have successfully identified genetic associations with withdrawn behavior, despite the abundance of evidence of its heritability. This may be due to reliance of categorical over dimensional measures of the behaviorally inhibited phenotype. The aim of this study is to identify associations between known psychiatric candidate genes and a dimensionally derived measure of withdrawn behavior. Methods Genetic information was collected on 20 single‐nucleotide polymorphisms (SNPs) from a custom‐designed SNP chip and TAQMAN arrays of 4 variable number of tandem repeat (VNTR) genes for 551 individuals from 187 families. Linear mixed modeling was employed to examine the relationship between genotypes of interest and Child Behavior Checklist (CBCL) Withdrawn Behavior Subscale Score (WBS) while controlling for gender and age through multiple linear regressions. Results Withdrawn behavior was highly associated with polymorphism rs6314 of the serotonin receptor 2A (HTR2A) [p = .009, estimate = 0.310 (bootstrap 95% CI 0.155–0.448), bootstrap p = .001] and rs1800544 of the alpha 2‐adrenergic (ADRA2A) [p = .001, estimate = −0.310 (bootstrap 95% CI −0.479 to −0.126), bootstrap p = .001] genes after correction for gender and age. The association between withdrawn behavior and ADRA2A was stronger for younger children. Conclusions HTR2A and ADRA2A genes are associated with withdrawn behavior. This reinforces the role of catecholaminergic genes in the heritability of withdrawn behavior.